1978
DOI: 10.1073/pnas.75.8.3771
|View full text |Cite
|
Sign up to set email alerts
|

Control of microtubule assembly-disassembly by calcium-dependent regulator protein.

Abstract: The Ca2+-dependent regulator (CDR) protein of cyclic nucleotide phosphodiesterase is a low molecular weight, acidic, Ca2+-binding protein which has been implicated in a number of Ca2+ dependent enzymatic functions. Indirect immunofluorescence has revealed that CDR is specifically associated with the chromosome-to-pole region of the mitotic apparatus during metaphase-anaphase in a pattern distinctly different from that of similar cultured cells stained with anti-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
173
0
1

Year Published

1979
1979
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 434 publications
(178 citation statements)
references
References 36 publications
4
173
0
1
Order By: Relevance
“…Examination of calcium sensitivity of cold labile microtubules demonstrated that calmodulin concentrations severalfold in excess of that of tubulin were required for disassembly (15). I now show that a calcium-and calmodulin-dependent protein kinase with broad substrate specificity can phosphorylate MAP-2.…”
mentioning
confidence: 94%
“…Examination of calcium sensitivity of cold labile microtubules demonstrated that calmodulin concentrations severalfold in excess of that of tubulin were required for disassembly (15). I now show that a calcium-and calmodulin-dependent protein kinase with broad substrate specificity can phosphorylate MAP-2.…”
mentioning
confidence: 94%
“…Studies in detergentextracted cells showed that microtubules polymerize at low calcium concentrations, whereas increasing calcium concentrations to the micromolar range directly induced microtubule disassembly (Fuller and Brinkley, 1976;Schliwa, 1976). These effects have been hypothesized to be mediated by calcium-dependent regulators of microtubule assembly, such as the abundant neuronal protein calmodulin (Marcum et al, 1978;Schliwa et al, 1981;Lee and Wolff, 1982;Deery et al, 1984). A recent report furthermore suggests that posttranslational modifications that are associated with microtubule stability, such as glutamylation, are regulated by synaptic activity (Maas et al, 2009).…”
Section: Nmda Receptor Activation Suppresses Microtubule Growth In Dementioning
confidence: 99%
“…Ca"-transport in erythrocytes (15) and sarcoplasmic reticulum (18), phosphorylation of synaptic and cell membranes (30,31), and the disassembly of microtubules (26). The mode of action of calmodulin on these systems has not been established .…”
mentioning
confidence: 99%